2019
DOI: 10.1038/s41467-018-07646-4
|View full text |Cite
|
Sign up to set email alerts
|

Manganese based layered oxides with modulated electronic and thermodynamic properties for sodium ion batteries

Abstract: Manganese based layered oxides have received increasing attention as cathode materials for sodium ion batteries due to their high theoretical capacities and good sodium ion conductivities. However, the Jahn–Teller distortion arising from the manganese (III) centers destabilizes the host structure and deteriorates the cycling life. Herein, we report that zinc-doped Na0.833[Li0.25Mn0.75]O2 can not only suppress the Jahn–Teller effect but also reduce the inherent phase separations. The reduction of manganese (III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
181
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(191 citation statements)
references
References 55 publications
(54 reference statements)
5
181
0
1
Order By: Relevance
“…The larger ionic radius of sodium ion (1.02 Å) compared to lithium ion (0.76 Å), however, has been regarded as the greatest challenge to hinder the performance improvement of sodium‐ion batteries . In the past ten years, a lot of works focused on seeking for appropriate Na + ‐host materials, such as transition‐metal oxides, phosphates, and ferrocyanides . Among them, the Fe‐based phosphate is one of the most concerned cathode materials due to its low cost and abundant resources .…”
Section: Introductionmentioning
confidence: 99%
“…The larger ionic radius of sodium ion (1.02 Å) compared to lithium ion (0.76 Å), however, has been regarded as the greatest challenge to hinder the performance improvement of sodium‐ion batteries . In the past ten years, a lot of works focused on seeking for appropriate Na + ‐host materials, such as transition‐metal oxides, phosphates, and ferrocyanides . Among them, the Fe‐based phosphate is one of the most concerned cathode materials due to its low cost and abundant resources .…”
Section: Introductionmentioning
confidence: 99%
“…Also, since both sodium and potassium have large ionic radii, strong Na + −Na + /K + −K + interactions will occur, and this phenomenon requires strongly hybridized orbitals of central elements to accommodate them. [ 36 ] Manganese is another ideal element to address this issue; [ 37–41 ] but the Jahn–Teller effect of Mn 3+ (both octahedral high spin and low spin d 4 electrons) cannot be perfectly avoided during electrochemical processes, which will lead to unstable local coordination structures and inferior cycling performance. [ 42 ] Vanadium only possesses three d‐orbital electrons and will not be bothered by this issue.…”
Section: Scientific Importance Of Vanadium‐based Composites For Buildmentioning
confidence: 99%
“…The soft XAS spectra indicated that the increased Cu content could enhance the metal to ligand charge transfer (MLCT) effect, and the O K‐edge also showed that Cu−O becomes a redox centre compensating for charge neutrality (as a result of Fe ion migration). It can be deduced that other transition metal elements such as Zn, Ti, and Ru will also have positive effects on the voltage decay mentioned above . Multiple element doping can also reduce the Jahn‐Teller effect.…”
Section: Xas Techniques For Sodium Layered Transition Metal Oxidesmentioning
confidence: 99%
“…Mn is troublesome sometimes since the strong Jahn‐Teller effect from manganese (III) centres can destabilize host structures. Very recently, Kang's group reported that Li/Zn substitution can be an effective way to reduce the inherent phase separation . A high binding energy was confirmed, and octahedral structure variations were reduced.…”
Section: Xas Techniques For Sodium Layered Transition Metal Oxidesmentioning
confidence: 99%
See 1 more Smart Citation